Transforming learning with meaningful technologies : 14th European Conference on Technology Enhanced Learning, EC-TEL 2019, Delft, The Netherlands, September 16-19, 2019, Proceedings /: 14th European Conference on Technology Enhanced Learning, EC-TEL 2019, Delft, The Netherlands, September 16-19, 2019, Proceedings. (2019) - Unknown
No abstract available